Effects of Lower Limb Endurance Training on Maximal Oxygen Uptake (VO2 max) in Chronic Obstructive Pulmonary Disease - Andika Pradana; Amira P Tarigan; Tari Mediyanti; Erna Mutiara; Pandiaman Pandia (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2017)
Background: Patients with COPD exhibit muscle atrophy and dysfunction which lead into decondition state. This will in turn decrease maximal oxygen uptake (VO2 max) in tissues. Considered as the best predictor of cardiorespiratory endurance and survival, VO2max can be attenuated by aerobic training. This study aimed to assess the effects of lower-limb endurance training on VO2 max in COPD patient. Methods: An experimental study was conducted on 20 COPD patients in group C and D in June–July 2017 at USU Hospital. Patients were prescribed lower-limb exercise by stationary cycling with individualized dose, twice a week for 4 weeks, ranging from 5-20 minutes/session. VO2 max measurement was calculated pre-and post-intervention using Nury’s Formula specifically designed for Indonesian (r=0,68; P